Macroalgas del arrecife coralino de Cabo Pulmo-Los Frailes, B.C.S., México - Anaya Reyna, Gabriela (Universidad de Costa Rica, 1996)
Non-systematic surveys of the Cabo Pulmo-Los Frailes coral reef (1988 to 1994) incrcased to 61 the number of macroalgal species: 11 Chlorophyta, 11 Phaeophyta, and 39 Rhodophyta. Like other reefs, ¡his was dominated by filamentous species that occurred as mutispecies turfs. Unlike other reefs, this assembly is mude up 01' temperate, cosmopolitan and tropical species.